Main directions of improving Ukrainian legislation on information security in war conditions - Horulko, V. V. (Науковий вісник Ужгородського національного університету. Серія Право, 2025)
The article is dedicated to a comprehensive legal analysis of the challenges facing Ukraine’s information security during wartime and the development of legal mechanisms to enhance the regulatory framework for effectively safeguarding the information space. The study examines hybrid threats, including cyberattacks on critical infrastructure, disinformation campaigns on social media, and cyber sabotage, through the lens of law enforcement practices based on real cases from 2022–2023, such as attacks on “Ukrenergo” and the “Diia” system. The current legislation, encompassing the Laws of Ukraine “On Cybersecurity” and “On Information,” is evaluated, revealing significant legal shortcomings: normative conflicts, outdated provisions, insufficient adaptation to martial law conditions, and a lack of regulation for emerging technologies like artificial intelligence in cyberattacks. Drawing on an analysis of judicial practice, official reports from the State Service of Special Communications and Information Protection, the Center for Strategic Communications, and international standards such as the EU NIS2 Directive and NATO Cybersecurity Strategy, five key legal reforms are proposed. These include: integrating blockchain technologies into the legal regulation of data protection to prevent information leaks, establishing an international cybersecurity hub as a legal entity with authority for international cooperation, introducing the legal category of “cyber-psychological aggression” to combat disinformation, developing legal mechanisms to enhance public cyber literacy through mandatory educational programs, and strengthening sanctions for cyber offenses by introducing “digital sanctions” and the category of “cyber sabotage” into the Criminal Code. Special emphasis is placed on the legal adaptation of legislation to martial law conditions, necessitating rapid responses to threats and coordination among the state, private sector, and international partners. A detailed roadmap for legal reforms is proposed, outlining specific implementation stages until 2027, accompanied by effectiveness forecasts predicting a 50% reduction in cyber offenses. The article targets lawyers, researchers, IT specialists, and public officials engaged in developing and implementing legal tools to protect Ukraine’s information space amid wartime conditions.